Energy Yield Modeling for Optimization and Analysis of Perovskite‐Silicon Tandem Solar Cells Under Realistic Outdoor Conditions. Issue 4 (5th February 2023) - Tomšič, Špela; Jošt, Marko; Brecl, Kristijan; Topič, Marko; Lipovšek, Benjamin
Abstract: A comprehensive algorithm for calculating the energy yield ( EY ) is used as the most important figure‐of‐merit in determining the capabilities of PV devices in realistic operation. The model is based on advanced optical modeling and extensive opto‐thermo‐electrical characterization. It takes the realistic environmental and device installation data fully into account, as well as the complete set of device specifications including all relevant temperature‐induced variations. A detailed analysis and optimization of two‐terminal perovskite‐silicon tandem devices are done in terms of long‐term electrical energy production at different geographical locations from distinct Köppen–Geiger–Photovoltaic climate zones (KGPV). It is shown that the optimal perovskite bandgap ( E G, PK ) in a tandem device operating under realistic conditions is in all cases higher than the one optimized under STC, yet does not differ significantly from location to location, which is beneficial from the manufacturing point of view. The optimal E G, PK is influenced primarily by the spectral distribution of incident irradiance, and not so much by the operating temperature conditions. Moreover, a clear linear dependency between the optimal E G, PK and the weighted average photon energy of the incident irradiance is demonstrated, which presents an important rule for rapid tandem design. Abstract : A comprehensive algorithm is developed for calculating the energy yield as the figure‐of‐merit in determining the capabilities of perovskite‐silicon tandem photovoltaic devices in realistic operation. It is based on advanced optical modeling and extensive opto‐thermo‐electrical characterization. State‐of‐the‐art tandem solar cells are analyzed and optimized for different locations, and a clear set of design guidelines is derived.